SERVICE USERS' FAMILIES' CONCEPTIONS OF THE CARE OFFERED IN A PSYCHO-SOCIAL CARE CENTER - Renata Cavalcanti Cordeiro; Priscilla Maria de Castro Silva; Elisângela Braga Azevedo; Maria de Oliveira Ferreira Filha; Raissa Barbosa de Andrade; Johana Maria Oliveira de Andrade (Universidade Federal do Paraná, 2013)
This is an exploratory case study with a qualitative approach, undertaken in a psycho-social care center in the North-Eastern region of Brazil, with 20 family members of service users. The objective was to analyze their conceptions regarding the care offered; to identify whether the family members perceived that the professionals at the Center contribute to the promotion of the service users' autonomy and social inclusion; and to check to what extent the family group has been an efficient strategy for promoting the care for the service users. The empirical material was produced through semi-structured interviews held between August and September 2010, and submitted to content analysis. The results show that the participation in the family group made it possible for families to contribute to the treatment proposed, becoming co-responsible in the care process offered. The family members were encouraged to promote the service user's autonomy and inclusion in society.